Manifestation of Skin Disorders in HIV & AIDS Patients - Listiana Dewi, Indah Sari; Hidayati, AÃ¯Â¬Âf Nurul (Faculty Of Medicine Airlangga University, 2015)
Background: Human immunodeï¬ciency virus (HIV) can causes deï¬ciency of cellular immunity resulting in decreased +lymphocyte T helper (CD4 T cell). Most common infections and neoplastic process of skin in HIV patients were facilitated by loss of CD4 in immune system. Skin disorders are often found in patients with HIV/AIDS, so that the necessary understanding and evaluation are needed for better management. Methods: Descriptive retrospective study using medical records of patients diagnosed with HIV & AIDS related skin disorders in Intermediate Unit Care of Infection Disease Ward, Dr. Soetomo General Hospital, Surabaya in 2013. The type of skin disorder, aged, supporting examination, transmission factors, CD4 counts, and therapy were recorded. Results: HIV & AIDS patients in 2013were about 649 patients, 301 patients (46.3%) among of them suffered from skin disorders. Most of them were in 25-44 years of age (70.8%). The most common skin disorders were oral candidiasis (81.1%). Examinations were performed (52.8%) to conï¬rm the diagnose. Most of transmission factors were well3 known (66.1%). CD4 count cell were clearly noted only 17.3% in medical record, and 12.2% in CD4 1-100 sel/mm. There were 31.6% of patients received ARV. Conclusions: Skin disorders are most common disorders in HIV & AIDS patients and are determined by CD4 count. Oral candidiasis is most common skin and mucocal disorder in HIV & AIDS patient. Key words: HIV-AIDS, skin disorders, CD4+ T cells, oral candidiasis,retrospective study.